Konstruowanie projektu pracy dyplomowej jako element kształcenia akademickiego prz yszłych naucz ycieli jęz yków obcych - Orchowska, Izabela (Neofilolog, 2010)
The aim of the article is to answer the question if and to what extent preparing a diploma project on glottodidactics should be an opportunity for the student trainee to understand glottodidactics as a scholarly domain. The author of the article assumes that student’s understanding of the specificity of glottodidactics depends on their developing the so called general epistemological consciousness. The student should gradually develop the awareness of how a researcher epistemological perspective influences the posed research questions and the interpretation of analyzed phenomena as well as the construction of knowledge of and beliefs about the process of learning/teaching a foreign language. To illustrate the problem, the article refers to specific diploma work projects whose authors are the student trainees of the French section at the College of Foreign Languages at UAM in Poznań.